Prehypertension and hypertension among the medical students of public medical colleges in Dhaka, Bangladesh: A cross-sectional study (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: Prehypertension and hypertension are the leading risk factors for cardiovascular diseases and are increasingly prevalent among young adults. This study aimed to assess the prevalence of prehypertension and hypertension among medical students of public medical colleges in Dhaka city, Bangladesh.Methods: This cross-sectional study was done among 293 medical students of four public medical colleges in Dhaka city. Data on age, sex, physical activity, smoking, alcohol consumption, height, weight, and blood pressure were obtained. Systolic blood pressure (SBP) of 120–139 mmHg or diastolic blood pressure (DBP) of 80–89 mmHg was considered prehypertensive, while SBP ≥140 mmHg or DBP ≥90 mmHg was classified as hypertensive.Results: The average age was 21.6 years. More than one-fourth (28.0%) were prehypertensive, and 4.8% were hypertensive. Multinomial logistic regression identified male sex (adjusted odds ratio, 4.6; 95% confidence interval, 2.5–8.3) and overweight (aOR 2.0; 95% CI 1.1–3.5) as the risk factors of prehypertension. For hypertension, the risk factors were male sex (aOR 9.7; 95% CI 2.3–42.0), ever alcohol consumption (aOR 18.0; 95% CI 1.3–249.8), and overweight (aOR 6.6; 95% CI 1.3–32.6).Conclusion: We report that one-third of the medical students have prehypertension and hypertension. Overweight and alcohol consumers should be considered for targeted intervention.